SQ3R Method as A Solution To Improve Reading Comprehension Skills in Elementary School - Rini Endah Sugiharti; Ratna Duhita Pramintari; Intan Destianingsih (Indonesian Journal of Primary Education, 2020)
The Scientific Work (KTI) is entitled "SQ3R methods as a solution to better reading skills in elementary school students." One important aspect of Indonesian learning is reading, by reading it can know things that are not yet known. Observations show that students occur in class IV SDN Jakasampurna V, reading skills of low comprehension: 1) Students have difficulty locating points of thought on text, 2) Students have difficulty capturing implied meanings and letters on text, 3) Students have difficulty making a summary on the reading text, and 4) Students have difficulty explaining the text text again. One contributing factor is that teachers continue to use traditional methods or read in moderation so that the learning process is ineffective, and the teacher and student interaction is lacking. One method for improving the learning skills of reading understanding is the SQ3R method which is a strategy for actively studying the text and leads directly to the essence or content of the underlying material. The step-by-step of the SQ3R method is the introductory (surveys), the raised question (question), the reading stage (reading), the answering of the question (slight), the reviewing of the review. The expected that students are able to: 1) To determine the point of thought correctly, 2) To grasp the corresponding meaning and implied meaning found in the reading text, 3) To summarize the reading text correctly, 4) To restate the reading text in its own sentences correctly. The step-by-step of the SQ3R method is the introductory (surveys), the raised question (question), the reading stage (reading), the answering of the question (slight), the reviewing of the review. The expected that students are able to: 1) To determine the point of thought correctly, 2) To grasp the corresponding meaning and implied meaning found in the reading text, 3) To summarize the reading text correctly, 4) To restate the reading text in its own sentences correctly. The step-by-step of the SQ3R method is the introductory (surveys), the raised question (question), the reading stage (reading), the answering of the question (slight), the reviewing of the review. The expected that students are able to: 1) To determine the point of thought correctly, 2) To grasp the corresponding meaning and implied meaning found in the reading text, 3) To summarize the reading text correctly, 4) To restate the reading text in its own sentences correctly.